Improvement of aquatic vegetation in urban waterways using protected artificial shallows - Weber, Arnd; Lautenbach, Sven; Wolter, Christian (Ecological engineering, 2012)
Wave- and current-protected shallows have been constructed in the heavily modified, urban River Spree to create a littoral habitat with reduced hydrodynamical disturbances by navigation. Five years after construction and an initial planting of various macrophytes, abiotic conditions were measured and the establishment of aquatic and riparian vegetation was assessed. This study aimed to quantify the effective reduction of hydrodynamic disturbances and to assess the rehabilitation of aquatic plants and the improvement of the macrophytes-based ecological status by means of the reference index (RI). Wave stress has been successfully reduced and a diverse, abundant community of aquatic and riparian plants developed resembling the vegetation of natural oxbows. Most of the planted species were still present after five years, and in addition, several new species became established. The aquatic plants at the rehabilitated site indicated a “good” ecological status and even the “high” status if planted species were excluded from the RI. In contrast, the control site remained largely unvegetated indicating a “bad” status. Abiotic conditions other than wave action confirmed low hydrological connectivity and the ecosystem-engineering capabilities of vegetation. Low oxygen saturation and the accumulation of organic material limit the habitat suitability for other biota. Principally, wave-protected shallows are well suited to improve aquatic macrophytes in urban waterways. They will be rapidly naturally colonized, while planting of macrophytes, especially of species typical for advanced stages of succession should be omitted.